Analysis of Teacher's Readiness for 2013 Curriculum Thematic Learning in SD Negeri 04 Kriyan Kalinyamatan Jepara - Rahmawati, Zuli Agustin; KHB, Moh Aniq; Endah H, Diana (Journal of Education Reseach and Evaluation, 2019)
This research was motivated by the readiness of teachers in the implementation of the 2013 curriculum thematic learning at SD Negeri 04 Kriyan Kalinyamatan Jepara. The problem in the research is "how is the readiness of the teacher towards the implementation of the 2013 curriculum thematic learning in class I to IV SDN 04 Kriyan Kalinyamatan Jepara?". The purpose to be achieved in this study is to describe the readiness of teachers in the 2013 curriculum thematic learning at SD Negeri 04 Kriyan Kalinyamatan Jepara. The method in this study is descriptive research that uses a qualitative approach, the subjects in this study were principals and teachers of Public Elementary School 04 Kriyan Kalinyamatan Jepara. The data in the research are all related instruments about the readiness of teachers in the 2013 curriculum thematic learning at SD Negeri 04 Kriyan Kalinyamatan Jepara. Sources of data obtained through questionnaires, observation, interviews and documentation. Checking data by extending observations, increasing perseverance, triangulating data, peers, holding member checks. while the data analysis techniques go through the stages of data reduction, data presentation, and verification / conclusion. The results of this study indicate that according to the observations I made to different teachers and classes 5 respondents were ready to carry out the 2013 curriculum thematic learning which can be seen from the range of scores that I have analyzed, namely 5 respondents get a range of scores A (Very Good) with scores between 90 ≤ A≤ 100 from the process of implementing learning and learning instruments. Become a researcher through observasil results from the assessment of learning devices and learning implementation instruments. This is to measure the readiness of teachers in the 2013 curriculum thematic learning at SD Negeri 04 Kriyan Kalinyamatan Jepara. Based on the results of this study, the suggestions that can be conveyed are that teachers are more able to increase the creativity of thematic learning with more challenging and maximum readiness in the 2013 curriculum thematic learning process so that it can run well.